Alkali metal ion binding using cyclic polyketones. Issue 18 (16th February 2022) - Ozawa, Narito; Shivakumar, Kilingaru I.; Murugavel, Muthuchamy; Inaba, Yuya; Yoneda, Tomoki; Ide, Yuki; Pirillo, Jenny; Hijikata, Yuh; Inokuma, Yasuhide
Abstract : Cyclic polyketones composed of acetylacetone analogues showed crown ether-like alkali metal ion binding in less polar solvents. Their cation-binding properties were used for the Finkelstein reaction and the design of new cation-binding hosts. Abstract : Cyclic oligoketones composed of 3, 3-dimethylpentane-2, 4-diones showed crown ether-like alkali metal ion binding behavior with association constants up to 1.7 × 10 4 M −1 in chloroform/acetonitrile (v/v, 9/1). The binding properties have been used for catalysis in the Finkelstein reaction in a low-polarity solvent. Furthermore, novel ion-binding hosts were generated by terminal functionalization of linear polyketones.